Meta-Analysis of Work Life Balance Policies and Their Impact on Employee Well Being - Jamaluddin; Suhardy; Sidrotun Na'im; St.Hatidja; Djunaedi; Andi harmoko arifin; Yusuf Bahtiar (eScience Humanity Journal, 2024)
This study aims to determine the impact of work-life balance policies on employee welfare. Along with the growing awareness of the importance of work-life balance, various policies have been implemented by companies to support the well-being of employees. This study collects and analyzes data from various studies that have been published to evaluate the effectiveness of such policies in improving employee well-being. The results of the analysis show that the work-life balance policy is significantly positively correlated with the improvement of employee welfare, which includes physical, mental, and emotional aspects with a Hedge's effect size value (d) of 0.891 in the high effect size category. In addition, this study also identifies several moderation variables such as the type of industry, the size of the company, and the type of policy that affects the effectiveness of the policy. These findings have practical implications for company management in designing and implementing effective work-life balance policies to support employee welfare